A study on abrasive water jet machining of aluminum with garnet abrasives - Khan, Ahsan Ali; Munajat, Noraziaty; Tajudin, Harnisah (Asian Network for Scientific Information, 2005)
In this study the effect of some cutting variables on the quality of the surface pnxiuced during abrasive water jet machining of aluminum has been investigated. The type of abrasive used was gamet of mesh size 80. The machining was done on the abrasive water jet machine WJ4080. The cutting variables were stand-off distance of the nozzle from the work surface. work feed rate and jet pressure. The evaluating criteria of the surface produced were width of cut, taper of the cut slot and work surface roughness. It was found experimentally that in order to minimize the width of cut; the nozzle should be placed close to the work surface. Increase in jet pressure results in widening of the cut slot both at the top and the at exit of the jet from the work. However. the width of cut at the bottom (exit) was always found to be larger than that at the top (at a stand-off distance of 3 mm and the work feed rate of 15 mm min-I). It was found that the taper of cut gradually reduces with increase in stand-off distance and was close to zero at the stand-off distance of 4 nun (at ajetpressure of 30 ksi and a work feed rate of 15 mm min-I). The feed rate of the work should be kept within 40 rum min- I (at the jet pressure of 30 h i and the stand-off distance of3 mm). because a feed rate beyond 40 mm min-I results in sharp increase in taper angle. The jet pressure does not show significant influence on the taper angle within the range of work feed and the stand-off distance considered. Both stand-off distance and the work feed rate show strong influence on the roughness of the machined surface. It was concluded that stand-off distance should be kept within 3 mm (at aiet pressure oDD ksi and a work feed rate ofl5 mm min-') and the work feed rate should be kept within 30 rum min-I (at ajetpressure of 30 hi and a stand-off distance of 3 nun) in order to have a good surface finish, since beyond those values of the parametern the roughness of the machined surface rises sharply. Increase in jet pressure shows positive effect in tenus of smoothness of the machined surface. With increase in jet pressure, the surface roughness decreases (at a stand-off distance of3mm and work feed of 15 mm min-I). This is due to fragmentation of the abrasive particles into smaller sizes at a higher pressure and due to the fact that smaller particles produce smoother surface. It was also found that within the jet pressure considered, the work surface is smoother near the top surface and gradually it becomes rougher at higher depths.